Some Lasting Effects of Undergraduate Economics on Retirement Planning - Bosshardt, William; B.Walstad, William (American Economic Review, 2017)
This study investigated the likely effects of undergraduate economics on whether a college graduate has opened a retirement account four years after graduation. Economic education is measured by the number of economics credit hours or whether a college graduate had majored in economics. Additional control variables for the logit analyses include occupation differences, employment record, and some demographics. Completing an undergraduate course in economics is significantly associated with having a retirement account, and economics majors are more likely than some other majors to have a retirement account. The analysis uses college transcript data from the Baccalaureate and Beyond study ( nces.ed.gov/surveys/b&b/ ).